Can National Health Insurance Pave the Way to Universal Health Coverage in Sub-Saharan Africa? - Cheryl Cashin; Jean-Paul Dossou (Taylor & Francis Group, 2021)
Countries of sub-Saharan Africa are increasingly turning to public contributory health insurance as a mechanism to advance UHC goals. Eight countries in sub-Saharan Africa have introduced national health insurance (NHI) systems, and at least seven more have plans or have passed legislation to establish NHI. Examining the experience of countries that have taken this path, some lessons emerge about whether and how contributory national health insurance may or may not be a viable path toward UHC in sub-Saharan Africa. Only Gabon, Ghana and Rwanda have been able to extend NHI coverage to a significant share of the population. None of the countries with NHI have peformed better on other UHC indicators-resource mobilization, service coverage and financial protection-than higher performing countries of Africa that did not introduce NHI. The experience of Gabon, Ghana and Rwanda provide lessons for what may be required to make NHI a viable path to UHC-there need to be explicit objectives and an understanding of why NHI can meet those objectives in the country's particular context; it must include key pro-equity design elements; and NHI needs to be supported by widespread political commitment and ongoing learning and adaptation. For many governments, achieving this kind of enabling environment for NHI may be particularly challenging for various political, economic, or social reasons. In these contexts, health sector leaders may consider looking inward to their existing health financing systems for ways to improve and be more effective.